Alternate wetting and drying decreases arsenic content and increases yield of rice grown in organic matter amended soil - Khan Md Abrarur Rahman; Mohammad Golam Kibria; Md Hosenuzzaman; Mahmud Hossain; Md Anwarul Abedin (Eurasian Journal of Soil Science, 2024)
Organic matter (OM) shows a critical role in mobilization and uptake of arsenic (As) by rice, and water management practice can mitigate this problem. However, very few research highlighted the impact of management of water on rice as influenced by OM amendment. Therefore, this study has evaluated the changes in As mobilization in paddy soil under different OM amendment and water management practices. Here, rice was grown to maturity in a two-factorial pot experiment comprising two different water management practices [continuous flooding (CF) and alternate wetting drying (AWD)] and eight combinations of As and OM amendment [comprising two As treatments (0 and 20 ppm) and four OM amendments (0, 0.25%, 0.5% and 5.0% w/w)]. Application of OM in As contaminated soil caused a significant increase in As accumulation in rice, and exhibited decreased growth and yield of rice. However, the results showed that rice growth and yield was significantly higher under AWD practice compared to CF. Arsenic concentration in rice was the lowest in As and OM control pots (44.67 µg/kg in AWD and 62.13 µg/kg in CF), and higher in As treated pots. Moreover, As concentration in rice grain increased with increasing levels of OM amendment. The As concentration in rice grain (168.44 µg/kg in AWD and 183.85 µg/kg in CF) was significantly higher in As treated pots with 0.5% OM amendment compared to other treatment combinations. Application of 5% OM in As contaminated soil did not produce any grains due to extreme toxicity. Thus, As accumulation in rice can be decreased by AWD water management technique without compromising yield. The findings suggest that applying OM in paddy soils with high soil As content should be done with caution.